Sistem Pendukung Keputusan Penerimaan Beasiswa di SMK 6 Kupang menggunakan Metode Analytical Hierarchy Process (AHP) - Jamung, Maria Susanti; Leosae, Sepriono; Babis, Arjen Yohanes; Mone, Gerry; Kaesmetan, Yampi R (Yayasan Kawanad, 2024)
Appreciation for students to excel by schools through school committees needs to be given to increase student motivation and enthusiasm for learning. The granting of a committee's money acquisition scholarship is expected to encourage students to continue to improve their achievements. Students receiving school committee scholarships are selected based on certain criteria set by SMK 6 Kupang. However, the selection process that is still manual faces obstacles such as long management and subjectivity in assessment. Therefore, a better alternative system is needed for the management of school committee scholarship recipients. The Analytical Hierarchy Process (AHP) method in the Decision Support System (SPK) can provide the best results so that students who really deserve a scholarship. The decision support system at SMK 6 Kupang determines the recipient of the School Committee scholarship based on criteria such as report cards, academic achievement, and non-academic achievements with the determined assessment weight. The calculation results show the final value based on the ranking, which is 0.3925 for ranking one, 0.2150 for rank two, and 0.1434 for third place. Based on the results of this ranking, a scholarship recipient has been selected in accordance with the established criteria.